Computer self-efficacy and computer attitude as correlates of internet use of secondary school students’ in Nigeria (2016)
The Internet as a useful tool that supports teaching and learning is not in full use in most secondary schools in Nigeria hence limiting the students from maximizing the potentials of Internet in advancing their academic pursuits. This study, therefore, examined the extent to which computer self-efficacy and computer attitude influence Internet use among senior secondary school students (SS1 and SS11) in public secondary schools in Lagos State, Nigeria. This study utilized the descriptive survey research design of the ex-post-facto type. Instruments used to collect data were Computer Self-Efficacy (CSE) (r=0.73), Computer Attitude (CATT) (r=0.85), and Internet Use (IU) (r=0.78)) scales. Data were analyzed using descriptive statistics, Pearson’s Product Moment Correlation and Multiple regressions at 0.8 level of significance. The relative contributions of the independent measures of Internet use were: CSE (β= .319, t=7.712), and ATC (β=-.099, t=3.085). The Computer Self-Efficacy, and Computer Attitude of senior secondary school students significantly influenced Internet use (F (3,559) = 60.064) respectively.